Tratamento da toxoplasmose ocular adquirida : revisão sistemática - Lima, Guilherme Sturzeneker Cerqueira (2017)
Ocular toxoplasmosis, a disease caused by the parasite Toxoplasma gondii, is the most common form of posterior infectious uveitis. Despite the fact that combined anti-parasitic therapy is still the usual practice regarding the treatment of ocular toxoplasmosis, there is no definitive evidence towards its routine necessity. The existence of multiple therapeutic schemes available nowadays has motivated the realization of this study, with the objective of trying to identify elements capable of guiding the physician to perform the best treatment in a case of ocular toxoplasmosis. It was concluded that there is no forceful scientific evidence that proves there is an ideal treatment and that there are no statistically significant differences between the functional outcomes obtained with the different therapeutic schemes employed in the present time.